Genomic signatures of Mannheimia haemolytica that associate with the lungs of cattle with respiratory disease, an integrative conjugative element, and antibiotic resistance genes - Clawson, M. L.; Murray, R. W.; Sweeney, M. T.; Apley, Michael D.; DeDonder, Keith D.; Capik, Sarah F.; Larson, Robert L.; Lubbers, Brian V.; White, Bradley J.; Kalbfleisch, T. S.; Schuller, G.; Dickey, A. M.; et al. (My University, 2016)
Background: Mannheimia haemolytica typically resides in cattle as a commensal member of the upper respiratory tract microbiome. However, some strains can invade their lungs and cause respiratory disease and death, including those with multi-drug resistance. A nucleotide polymorphism typing system was developed for M. haemolytica from the genome sequences of 1133 North American isolates, and used to identify genetic differences between isolates from the lungs and upper respiratory tract of cattle with and without clinical signs of respiratory disease. Results: A total of 26,081 nucleotide polymorphisms were characterized after quality control filtering of 48,403 putative polymorphisms. Phylogenetic analyses of nucleotide polymorphism genotypes split M. haemolytica into two major genotypes (1 and 2) that each were further divided into multiple subtypes. Multiple polymorphisms were identified with alleles that tagged genotypes 1 or 2, and their respective subtypes. Only genotype 2 M. haemolytica associated with the lungs of diseased cattle and the sequence of a particular integrative and conjugative element (ICE). Additionally, isolates belonging to one subtype of genotype 2 (2b), had the majority of antibiotic resistance genes detected in this study, which were assorted into seven combinations that ranged from 1 to 12 resistance genes. Conclusions: Typing of diverse M. haemolytica by nucleotide polymorphism genotypes successfully identified associations with diseased cattle lungs, ICE sequence, and antibiotic resistance genes. Management of cattle by their carriage of M. haemolytica could be an effective intervention strategy to reduce the prevalence of respiratory disease and supplemental needs for antibiotic treatments in North American herds.
Citation: Clawson, M. L., Murray, R. W., Sweeney, M. T., Apley, M. D., DeDonder, K. D., Capik, S. F., . . . Smith, T. P. L. (2016). Genomic signatures of Mannheimia haemolytica that associate with the lungs of cattle with respiratory disease, an integrative conjugative element, and antibiotic resistance genes. Bmc Genomics, 17, 14. doi:10.1186/s12864-016-3316-8
Keywords: Mannheimia; Haemolytica; Genomics; Polymorphisms; Genotypes; Subtypes